Big Five personality traits in simulated negotiation settings - Falcão, P. F. (2018)
Purpose: After a hiatus in the research on individual differences in negotiation, there has been a surge of renewed interest in recent years followed by several new findings. The purpose of this paper is to explore the effects that personality, as structured by the five-factor model, have over negotiation behavior and decision making in order to create new knowledge and prescribe advice to negotiators. Design/methodology/approach: This study replicates observations from earlier studies but with the innovation of using a different methodology, as data from a sample of volunteer participants were collected in regard to their personality and behavior during two computerized negotiation simulations, one with the potential for joint gains and the other following a more traditional bargaining scenario. Findings: Significant results for both settings were found, with the personality dimensions of agreeableness, conscientiousness, and extraversion systematically reoccurring as the most statistically relevant, although expressing different roles according to the type of negotiation and measure being registered. The findings thus suggest a multidimensional relationship between personality and situational variables in which specific traits can either become liabilities or assets depending upon whether the potential for value creation is present or not. Originality/value: The new findings on the impacts of personality traits on both distributive and integrative negotiations allow negotiators to improve their performance and to adapt to specific distributive or integrative negotiation situations.